42.1k views
1 vote
PLEASE HELPPPPPP !!!!!!

Write the equation of the graph shown below in factored form


f(x) = (x + 1)(x − 2)(x − 3)

f(x) = (x − 1)(x + 2)(x + 3)

f(x) = (x + 1)(x + 2)(x + 3)

f(x) = (x − 1)(x − 2)(x − 3)

PLEASE HELPPPPPP !!!!!! Write the equation of the graph shown below in factored form-example-1

1 Answer

4 votes

Answer:


f(x)=(x-1)(x-2)(x-3)

Explanation:

we know that

The x-intercepts or the roots of the function are the values of x when the value of the function is equal to zero

so

In this problem

Observing the graph

The x-intercepts are the points


(1,0),(2,0),(3,0)

so


x=1\\ x-1=0


x=2\\ x-2=0


x=3\\ x-3=0

therefore

The equation of the graph in factored form is equal to


f(x)=(x-1)(x-2)(x-3)

User Najim El Guennouni
by
5.3k points